Use of Clinical Isolates to Establish Criteria for a Mouse Model of Latent Cryptococcus neoformans Infection - Ding, Minna; Smith, Kyle D.; Wiesner, Darin L.; Nielsen, Judith N.; Jackson, Katrina M.; Nielsen, Kirsten (Frontiers in Cellular and Infection Microbiology, 2022)
The mechanisms of latency in the context of C. neoformans infection remain poorly understood. Two reasons for this gap in knowledge are: 1) the lack of standardized criteria for defining latent cryptococcosis in animal models and 2) limited genetic and immunological tools available for studying host parameters against C. neoformans in non-murine models of persistent infection. In this study, we defined criteria required for latency in C. neoformans infection models and used these criteria to develop a murine model of persistent C. neoformans infection using clinical isolates. We analyzed infections with two clinical C. neoformans strains, UgCl223 and UgCl552, isolated from advanced HIV patients with cryptococcal meningitis. Our data show that the majority of C57BL/6 mice infected with the clinical C. neoformans isolates had persistent, stable infections with low fungal burden, survived beyond 90 days-post infection, exhibited weight gain, had no clinical signs of disease, and had yeast cells contained within pulmonary granulomas with no generalized alveolar inflammation. Infected mice exhibited stable relative frequencies of pulmonary immune cells during the course of the infection. Upon CD4+ T-cell depletion, the CD4DTR mice had significantly increased lung and brain fungal burden that resulted in lethal infection, indicating that CD4+ T-cells are important for control of the pulmonary infection and to prevent dissemination. Cells expressing the Tbet transcription factor were the predominant activated CD4 T-cell subset in the lungs during the latent infection. These Tbet-expressing T-cells had decreased IFNγ production, which may have implications in the capacity of the cells to orchestrate the pulmonary immune response. Altogether, these results indicate that clinical C. neoformans isolates can establish a persistent controlled infection that meets most criteria for latency; highlighting the utility of this new mouse model system for studies of host immune responses that control C. neoformans infections.